Influence on motility of Escherichia coli and Salmonella typhimurium by a naturally occurring conjugative plasmid. - Bohlin, T (1977)
In a collection of 45 R-plasmids, one was found to be associated with loss of motility of its Escherichia coli K-12 and Salmonella typhimurium host bacteria when tested in conventional motility agar. Genetic experiments, as well as analyses of deoxyribonucleic acid, showed that inhibition of motility was caused by a conjugative plasmid that was separate from the R-plasmid. This second plasmid, named pUM5, was fi- and mediated the same type of sex pilus (F-like) as the accompanying R-plasmid but lacked resistance determinants. Preliminary studies indicated that bacterial cells carrying the motility inhibition plasmid pUM5 were still equipped with flagella. The mechanism by which flagellar action is disturbed by the plasmid is presently not known.